Implikasi Kesilapan Bertutur Bahasa Arab dalam Pemerolehan Makna - Hakim, Luthfi (Menara Tebuireng, 2022)
Abstract Speaking errors in language use cannot be separated from language competence. From the research conducted, there are several causes of errors, including due to mistakes (accident), lack of competence in the language or lack of proficiency in applying Arabic language rules in particular. Once the error can be identified, it will be easier to focus on handling it. This research uses qualitative methodology and descriptive analysis strategies. Then, there are three types of data collection methods: documentation, interviews, and observation. The data analysis strategy for this research is descriptive analysis. The results of this research show that the four main mistakes made by falsifiers in speaking a language are phonological, morphological, syntactic and semantic problems. Efforts to handle Arabic speech errors: Phonological Focus Training, Contextual and Situational Learning, Use of Error Analysis and Mastery Arabic grammar. Keyword: Implications, Arabic speech mistakes, meaning acquisition